Three New Carnivorous sponge species (Demospongiae: Cladorhizidae) from the Seamounts of the Central Indian Ridge - Rengaiyan, Periasamy; Ingole, Baban (Zootaxa, 2022)
Deep-sea sponges are an imperative component of benthos. They accumulate the suspended organic matter by filtering large quantities of water and, with their intricate structures, provide the most suitable habitats for various associated organisms. We describe three new cadorhizid sponges from the Central Indian Ridge (CIR), Indian Ocean. The sponges are part of the benthic sledge collection conducted onboard the MGS Sagar in the CIR region. A detailed taxonomic description of two novel species, Asbestopluma (Asbestopluma) indiyansis sp. nov., and Asbestopluma (A.) bharatiyae sp. nov. are provided based on the morphological and molecular (mtCOI and 28S) markers. In addition, another new carnivorous species Chondrocladia sagari sp. nov. is described based on the morphological and mtCOI marker. The systematic and descriptions of new species are discussed based on the structural and phylogenetic analysis. Our study shows that the cladorhizid fauna of the seamounts from the CIR are unique and represent regionally endemic benthic habitats.